The effect of l-arginine on erection time, sperm quality and the seminal plasma arginase activity in rams - Kaya, S. Ozer; Gur, S.; Kaya, E. (Ecole Nationale Veterinaire Toulouse, 2019)
The purpose of this study is to investigate the effects of L-arginine on sperm quality in the ram. Twelve Akkaraman fertile rams, 2-3 years old and weighing 50-60 kg, were divided into 2 lots: 6 treated and 6 controls. The treated animals were injected intramuscularly every 48 hours with 5 mg/ kg L-arginine; for 7 weeks; the witnesses an injection of isotonic saline of sodium chloride at the same rate. Semen was collected once a week in the presence of a sheep in heat (caused by an injection of prostaglandin). While intramuscular administration of L-arginine caused significant reduction in erection time (in 4th, 5th, 6th and 7th weeks) and abnormal spermatozoon ratio (only in 2nd week) when compared to control group, mass activity, motility, concentration (in 3th, 5th and 6th week), membrane integrity (in 4th, 5th, 6th and 7th weeks) were significantly increased. Consequently, intramuscular administration of L-arginine provides improvement in sperm quality parameters while reduces erection time in rams.
Keywords: L-arginine; sperm; arginase; ram